On the properly political (disposition for the) Anthropocene. (March 2019) - Blaser, Mario
The environmental crises referenced by the term Anthropocene incite responses that reflect different understandings about the right way to live on Earth. This, one would expect, should generate a proliferation of disagreements and an expansion of politics. Yet, so-called post-political authors warn that, instead, the way in which the Anthropocene has been brought to the public eye implies an emptying out of politics and a disavowal of the inherently conflictive pursuit of different visions about the right way to live on Earth. To counter this, they propose that the problematic of the Anthropocene needs to be displaced onto the terrain of the "properly political." In this paper I probe what the "properly political" might mean in the context of the Anthropocene.